Credit Market Constraints and Labor Market Decisions - Daniela Del Boca; Annamaria Lusardi (Institute for the Study of Labor (IZA), 2002)
In this paper, we examine whether imperfections in credit markets spill over to other markets, particularly the labor market. We take the case of Italy, a country that experienced changes in the mortgage market brought about by the 1992 European unification and other institutional shifts. These events make Italy a good laboratory to study the effects of financial markets on the labor market. Using a simultaneous equation framework and household data from the Bank of Italy between 1989 and 1993, we estimate the relationship between female participation and mortgage use. We find a significant impact of mortgages on women?s participation in the labor market.
Keywords: D91; J2; 330; mortgage market; female labor market participation; Realkredit; Verschuldungsrestriktion; Frauenerwerbstätigkeit; Arbeitsangebot; Schätzung; Italien